2003
DOI: 10.1354/vp.40-4-460
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and Immunologic Characteristics of Mouse × Cattle Xenogeneic Hybridomas Originating from Bovine Leukemia Virus-infected Cattle

Abstract: Abstract. Nine percent of xenogeneic hybridomas originating from a bovine leukemia virus (BLV)-infected cow secreted monoclonal IgM antibodies with multispecific reactivity. Similar reactivity was evident in some antibodies with an unusually long (Ͼ 50 amino acids) third complementarity-determining region of the heavy chain. Electron microscopy of hybridomas demonstrated the presence of c-type virus particles consistent with polymerase chain reaction detection of BLV env gene. Some hybridomas contained dilated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Questions remain as to how the bovine ultralong CDR H3 antibodies recognize antigen and what types of epitopes they recognize. Earlier work has indicated that the IgM antibodies BLV1H12 and BLV5B8 are multispecific, recognizing antigens such as DNA, synthetic haptens, and cytoskeleton proteins, and may be natural autoantibodies (1,42). Previous experiments with one ultralong antibody to the immunogen bovine viral diarrhea virus indicate that only CDR H3 is necessary for binding antigen (2).…”
Section: Discussionmentioning
confidence: 99%
“…Questions remain as to how the bovine ultralong CDR H3 antibodies recognize antigen and what types of epitopes they recognize. Earlier work has indicated that the IgM antibodies BLV1H12 and BLV5B8 are multispecific, recognizing antigens such as DNA, synthetic haptens, and cytoskeleton proteins, and may be natural autoantibodies (1,42). Previous experiments with one ultralong antibody to the immunogen bovine viral diarrhea virus indicate that only CDR H3 is necessary for binding antigen (2).…”
Section: Discussionmentioning
confidence: 99%
“…Antigen specificity of the Ab fragments was determined by ELISA against a panel of test Ags that included bovine actin, bovine thyroglobulin, bovine ubiquitin (all from Sigma, St. Louis, MO, USA), bovine IgG1 (Bethyl laboratories, Montgomery, TX, USA) and recombinant mycobacterial heat shock protein 65 (rHSP65; UNDP/WHO program, Geneva Switzerland). These antigens are known to be recognized by polyspecific BLV1H12 IgM antibody .…”
Section: Methodsmentioning
confidence: 99%